Degradation of carbon tetrachloride using ultrasound‐assisted nanoscaled zero‐valent iron particles@sulfur/nitrogen dual‐doped reduced graphene oxide composite: Kinetics, activation energy, effects of reaction conditions and degradation mechanism. (20th June 2019) - Meng, Fansheng; Ma, Yiyang; Wang, Yeyao
Abstract : We report a study of the synthesis of nanoscale zero‐valent iron particles stabilized by sulfur/nitrogen dual‐doped reduced graphene oxide (i.e. nZVI@SN‐rGO) and their applications as major reactants for the dechlorination of carbon tetrachloride (CT) by combining sonolysis with consideration of several operation parameters such as pH, temperature, catalyst dosage, as well as in the presence of common inorganic anions. The experimental results showed that the modified technology could remain effective for up to 180 min of reaction time under optimal conditions. Especially, there was no significant reduction in the removal efficiency toward CT even after five cycles, which was indicative of good stability. A study of the effects of common inorganic anions revealed that the presence of Clˉ and HCO3 ˉ exhibited different positive effects in the following order: Clˉ > HCO3 ˉ; NO3 ˉ and SO4 2 ˉ showed inhibition effects on CT removal. The structure and properties of nZVI@SN‐rGO were characterized using X‐ray diffraction, scanning electron microscopy, surface area analysis, Raman spectroscopy and X‐ray photoelectron spectroscopy. Additionally, the corresponding activation energy was approximately 31.04 kJ mol −1, suggesting that the surface chemical reaction rather than diffusion was the rate‐limiting step in the CT decomposition process. More importantly, the possible reaction mechanism and dechlorination pathway of CT using the ultrasound‐assisted nZVI@SN‐rGO system were also investigated. Abstract : The significant synergistic effect of sonolysis and nZVI@SNrGO combination on the degradation of CT was observed, and the corresponding calculated synergy factor was 1.45. The corresponding activation energy was approximately 31.04 kJ mol–1, suggestingthat the surface chemical reaction rather than diffusion was the ratelimitingstep in the CT decomposition process. The effects of common inorganic anions revealedthat the presence of Clˉ and HCO3ˉ exhibited different positive effects in thefollowing order: Clˉ > HCO3ˉ.